Culture a Law As Share Value System Advocate In Enforcement Law - Mustaqim Mustaqim; Yenny Febrianty; Mustika Mega Wijaya; Isep H Insan; Asmak Ul Hosna; Angga Perdana (Green Publisher Indonesia, 2023)
Life nation and society in Indonesia must be based on dimensions of culture so that own value system (value system) is something based on life balance between the interests of society and law, meaning the creation of law aims to guard the interest whole society like done by lawyers. Topic about How the role of the advocate in enforcement law? as well as discuss How analysis culture law as a value system for an advocate in enforcement law? become formula necessary problem discussed and analyzed in writing scientific this. The method of the study This wear kind of juridical normative, that is by conducting a number of studies on regulation legislation as well as references other For can facilitate the explanation process of culture law for advocating in progress enforcement law. Findings from discussion study This found that culture law for advocate in enforcement law is profession independent, free, and responsible answer To become an enforcer required law protection and guarantee from the country so Indonesian lawyers can help in a manner law society in need help law without exists discrimination belief, religion, descent, ethnicity, position social or belief politics.